OPTIMASI PROSES KONVERSI BIODIESEL DARI MINYAK JARAK DENGAN BIOKATALIS LIPASE CANDIDA SP - - Salmyah; - Syahiddin; Muhammad Zaki (Politeknik Negeri Lhokseumawe, 2014)
The research on the enzymatic synthesis of biodiesel from castor oil has been done. Some of the variables studied were the comparison of methanol and oil (X1), the amount of lipase enzyme (X2) and the reaction time (X3). The mathematical model that describes the relationship between the yield and the dependence variables was developed. According to the research, the yield of biodiesel obtained was in the range of 60% to 98%. The optimum conversion process was in the ratio methanol and oil of 5:1. Furthermore, the addition of 1 ml of enzyme and the reaction time of 12 hours produce 94% yield of biodiesel. Finally, the composition of the biodiesel was analyzed using Chromathography Mass Spectrometry, where palmitic acid 3.95% area, linoleic acid 7.14% area, 77.61% oleic acid area, and stearic acid 8.97% area was achieved